Use of ICT’s by Extension Personnel in Dissemination of Agriculture Information in North Eastern Karnataka - K.K. , Shashidhara (Indian Journal of Extension Education, 2020)
The study was conducted in North Eastern Karnataka and Raitha Samparka Kendra’s (RSKs) of Kalaburgi, Yadgir and Raichur districts. 55.97 per cent of the extension personnel belonged to medium level of ICT usage followed by low level (25.37%) and high level (18.66%) of usage. The extent of usage of ICT tools and services by the extension personnel in dissemination of agriculture information was positive and significantly correlated with the ICT services available (r=0.641), organization climate (r=0.475) and job commitment (r=0.591). Logit regression analysis show that independent variables contribute to 82.80 per cent of the variation in usage of ICT tolls and services by extension personnel in dissemination of agriculture information.
Keywords: ICT Usage; ICT tools and services; Extension personnel